Imaging Hallmarks of the Tumor Microenvironment in Glioblastoma Progression - Walsh, John J.; Parent, Maxime; Akif, Adil; Adam, Lucas C.; Maritim, Samuel; Mishra, Sandeep K.; Khan, Muhammad H.; Coman, Daniel; Hyder, Fahmeed (Frontiers in Oncology, 2021)
Glioblastoma progression involves multifaceted changes in vascularity, cellularity, and metabolism. Capturing such complexities of the tumor niche, from the tumor core to the periphery, by magnetic resonance imaging (MRI) and spectroscopic imaging (MRSI) methods has translational impact. In human-derived glioblastoma models (U87, U251) we made simultaneous and longitudinal measurements of tumor perfusion (Fp), permeability (Ktrans), and volume fractions of extracellular (ve) and blood (vp) spaces from dynamic contrast enhanced (DCE) MRI, cellularity from apparent diffusion coefficient (ADC) MRI, and extracellular pH (pHe) from an MRSI method called Biosensor Imaging of Redundant Deviation in Shifts (BIRDS). Spatiotemporal patterns of these parameters during tumorigenesis were unique for each tumor. While U87 tumors grew faster, Fp, Ktrans, and vp increased with tumor growth in both tumors but these trends were more pronounced for U251 tumors. Perfused regions between tumor periphery and core with U87 tumors exhibited higher Fp, but Ktrans of U251 tumors remained lowest at the tumor margin, suggesting primitive vascularization. Tumor growth was uncorrelated with ve, ADC, and pHe. U87 tumors showed correlated regions of reduced ve and lower ADC (higher cellularity), suggesting ongoing proliferation. U251 tumors revealed that the tumor core had higher ve and elevated ADC (lower cellularity), suggesting necrosis development. The entire tumor was uniformly acidic (pHe 6.1-6.8) early and throughout progression, but U251 tumors were more acidic, suggesting lower aerobic glycolysis in U87 tumors. Characterizing these cancer hallmarks with DCE-MRI, ADC-MRI, and BIRDS-MRSI will be useful for exploring tumorigenesis as well as timely therapies targeted to specific vascular and metabolic aspects of the tumor microenvironment.